PERSETERUAN BAHASA: SEBUAH KAJIAN LINGUISTIK FORENSIK ATAS WAWANCARA PENGACARA - Nuryani Nuryani; Monita Soleha (Balai Bahasa Provinsi Riau, 2023)
The feuds between lawyers of celebrities which often occurred recently is interesting to analyze because they grab public attention. This paper attempts to analyze the alleged defamation committed by Andar Situmorang against Hotman Hutapea, better known as Hotman Paris, when interviewed by journalists in front of the KPI office.. The method used is descriptive qualitative which allows researchers to describe the data in depth. The data collected is in the form of utterances delivered by research subject. In general, due to its relation to language problems in legal cases, this paper can be considered as a forensic linguistic study. To find out the aims of this study, several linguistic theories including cohesion, coherence, and cognitive semantics were used simultaneously. The analysis results show that the alleged defamation committed by Andar Situmorang against Hotman Hutapea can be proven linguistically.;Therefore, it is a proof that linguistic studies can be very helpful for investigating legal cases.